Intervening With Attachment and Biobehavioral Catch-Up to Reduce Behavior Problems Among Children Adopted Internationally: Evidence From a Randomized Controlled Trial. (August 2022) - Yarger, Heather A.; Lind, Teresa; Raby, K. Lee; Zajac, Lindsay; Wallin, Allison; Dozier, Mary
Children who have been adopted internationally often exhibit persistent behavior problems. The current study assessed the efficacy of the Attachment and Biobehavioral Catch-up intervention (ABC;Dozier & Bernard, 2019 ) for reducing behavior problems in 122 children adopted internationally. Behavior problems were measured via parent-report using the Brief Infant Toddler Social Emotional Assessment at a pre-intervention visit and after the intervention when children were between 18 and 36 months. Children's behavior problems were also observed using the Disruptive Behavior Diagnostic Observation Schedule (DB-DOS) after the intervention when children were 48 and 60 months. Parents who received ABC reported fewer child behavior problems than parents who received the control intervention immediately after the intervention through 1.5 years post-intervention. Additionally, children whose parents received ABC exhibited fewer behavior problems within the parent context of the DB-DOS when they were 48 months old (2 years post-intervention) than children whose parents received the control intervention. There were no significant intervention effects on children's observed behavior problems within the examiner contexts. These results support the efficacy of ABC in reducing behavior problems among children adopted internationally. Trial registration:ClinicalTrials.gov NCT00816621.